Hexamermis jengi n. sp. (Nematoda: Mermithidae) parasitizing grasshoppers and the invasive fall armyworm in Taiwan and Thailand - Ping-Chieh Lee; Ace Kevin S. Amarga; Wen-Hua Chen; Li-Hsin Wu; Chuan-Kai Ho; Chun-I Chiu; Ming-Chung Chiu (Journal of Invertebrate Pathology, 2026)

Characterization and biological activity of djulis (Chenopodium formosanum) phytosomes and in vivo cosmeceutical applications - Chien-Shan Chiu; Yung-Jia Chan; Min-Hsuan Wu; Bing-Lun Hua; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Bioscience, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Multidimensional riverine biodiversity reveals decadal and sub-decadal effects of hydrological and water-quality changes - Muhammad Farooq; Zihao Wen; Deep Narayan Shah; Ram Devi Tachamo-Shah; Debashis Kumar Mondal; Li Guili; Ming-Chih Chiu; Qinghua Cai (Environmental Research, 2026)

Synergistic quorum quenching effect and mechanism of penicillin G acylase combined with chlorogenic acid against Hafnia alvei and their application in salmon fillets preservation - Xinran Lv; Hengli Xu; Yichang Sun; Xin Wen; Minghan Shan; Wenjin Yan; Qihan Bai; Sicheng Li; Siyan Du; Xuepeng Li; Jianrong Li; Hung-chuan Chiu (Food Bioscience, 2026)

Integrated Multi-Endpoint Analysis of Soluble Copper(II) Chloride–Induced Oxidative Stress, Mitochondrial Dysfunction, and Genotoxicity in RAW264.7 Macrophages - Ping-Kun Tsai; Sheng-Wen Wu; Yen-Ju Lee; Yu-Ting Chang; Shiuan-Shinn Lee; Yung-Chuan Ho; Li-Chiu Yang; Yu-Hsiang Kuan (Biological Trace Element Research, 2026)

Thermal resistance and stability of multilayers embedding probiotic structure - Ping-Hsiu Huang; Chien-Shan Chiu; Wen-Chien Lu; Chang-Wei Hsieh; Po-Hsien Li (Journal of Food Engineering, 2026)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Effects of pyrolysis temperature on the biochar-derived horse manure: Physicochemical characteristics and catalytic activation of peroxymonosulfate activation toward sulfamethoxazole degradation in aqueous solution - Li-Min Chiang; Thanh-Binh Nguyen; Chiu-Wen Chen; Cheng-Di Dong; Chung-Hsin Wu (Journal of Water Process Engineering, 2025)

Advanced groundwater level forecasting with hybrid deep learning model: Tackling water challenges in Taiwan’s largest alluvial fan - Yu-Wen Chang; Wei Sun; Pu-Yun Kow; Meng-Hsin Lee; Li-Chiu Chang; Fi-John Chang (Journal of Hydrology, 2025)

Comparison of microwave-assisted and hot-air-drying method on the physicochemical properties and eating quality of rice bran noodles - Ping-Hsiu Huang; Yu-Tsung Cheng; Wen-Chien Lu; I-Yu Chiu; Chiun-Chung R. Wang; Po- Hsien Li (Food Bioscience, 2025)

AI-driven weather downscaling for smart agriculture using autoencoders and transformers - Pu-Yun Kow; Yun-Ting Wang; Yu-Wen Chang; Meng-Hsin Lee; Ming-Hwi Yao; Li-Chiu Chang; Fi-John Chang (Computers and Electronics in Agriculture, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Polystyrene microplastics induce hepatic lipid metabolism and energy disorder by upregulating the NR4A1-AMPK signaling pathway - Hui-Wen Chiu; Chun-Wei Chu; Chih-Chia Huang; Zi-Chun Chia; Yung-Li Wang; Yu-Hsuan Lee (Environmental Pollution, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

New perspectives on different Sacha inchi seed oil extractions and its applications in the food and cosmetic industries - Wen-Chien Lu; Chien-Shan Chiu; Yung-Jia Chan; Amanda Tresiliana Mulio; Po-Hsien Li (Critical Reviews in Food Science and Nutrition, 2025)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Oxidative stress and potential effects of metal nanoparticles: A review of biocompatibility and toxicity concerns - Yung-Li Wang; Yu-Hsuan Lee; Chu-Lin Chou; Yu-Sheng Chang; Wen-Chih Liu; Hui-Wen Chiu (Environmental Pollution, 2024)

High-spatiotemporal-resolution PM2.5 forecasting by hybrid deep learning models with ensembled massive heterogeneous monitoring data - Kuan-Yen Wu; I-Wen Hsia; Pu-Yun Kow; Li-Chiu Chang; Fi-John Chang (Journal of Cleaner Production, 2023)

Environmental melamine exposure and adverse kidney outcomes in patients with type 2 diabetes mellitus - Yi-Chun Tsai; Chia-Fang Wu; Wei-Wen Hung; Ping-Shaou Yu; Chia-Chu Liu; Tusty-Jiuan Hsieh; Chu-Chih Chen; Sih-Syuan Li; Jia-Jen Chen; Yi-Wen Chiu; Shang-Jyh Hwang; Ming-Tsang Wu (Environmental Pollution, 2023)

Therapeutic effects of green tea on endometriosis - Xiaoyan Chen; Gene Chi Wai Man; Sze Wan Hung; Tao Zhang; Linda Wen Ying Fung; Chun Wai Cheung; Jacqueline Pui Wah Chung; Tin Chiu Li; Chi Chiu Wang (Critical Reviews in Food Science and Nutrition, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

In vitro and in vivo anti-tumor activity of Coenzyme Q0 against TWIST1-overexpressing HNSCC cells: ROS-mediated inhibition of EMT/metastasis and autophagy/apoptosis induction - Hsin-Ling Yang; Li-Wen Chiu; Yi-An Lin; Sudhir Pandey; Chithravel Vadivalagan; Jiunn-Wang Liao; Yugandhar Vudhya Gowrisankar; Hui-Jye Chen; Hui-Yi Lin; You-Cheng Hseu (Toxicology and Applied Pharmacology, 2023)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Genomic characterization of a rare Carica papaya X chromosome mutant reveals a candidate monodehydroascorbate reductase 4 gene involved in all-hermaphrodite phenomenon - Jen-Ren Chen; Hiroki Ueno; Hideo Matsumura; Naoya Urasaki; Chen-Yu Lee; Fure-Chyi Chen; Shih-Wen Chin; Chun-Chi Liu; Chan-Tai Chiu; Kazuhiko Tarora; Jing-Yi Li; Chieh Ying Lee; et al. (Molecular Genetics and Genomics, 2021)

Composition of harvested seeds and seed selection by the invasive tropical fire ant, Solenopsis geminata (Hymenoptera: Formicidae) in Taiwan - Li-Chuan Lai; Ming-Chung Chiu; Chih-Wei Tsai; Wen-Jer Wu (Arthropod-Plant Interactions, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

Antibiotic resistance pattern and gene expression of non-typhoid Salmonella in riversheds - Chao-Yu Hsu; Bing-Mu Hsu; Wen-Tsai Ji; Jung-Sheng Chen; Tsui-Kang Hsu; Dar-Der Ji; Shao-Feng Tseng; Yi-Chou Chiu; Po-Min Kao; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

β2-Glycoprotein I inhibits VEGF-induced endothelial cell growth and migration via suppressing phosphorylation of VEGFR2, ERK1/2, and Akt - Wen-Chin Chiu; Jan-Yu Lin; Tzong-Shyuan Lee; Li-Ru You; An-Na Chiang (Molecular and Cellular Biochemistry, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A study of rationality of slopeland use in view of land preservation - Li-Ling Lin; Chao-Wen Wang; Cheng-Lung Chiu; Yung-Chuan Ko (Paddy and Water Environment, 2011)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

The Association of Metallothionein-4 Gene Polymorphism and Renal Function in Long-Term Lead-Exposed Workers - Hsin-I Chen; Yu-Wen Chiu; Yu Kuei Hsu; Wan-Fen Li; Yi-Chun Chen; Hung-Yi Chuang (Biological Trace Element Research, 2010)

A tomato bZIP transcription factor, SlAREB, is involved in water deficit and salt stress response - Tsai-Hung Hsieh; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Sanjaya; Yi-Chien Tsai; Ming-Tsair Chan (Planta, 2010)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Vibrational analysis of mandible trauma: experimental and numerical approaches - Shu-Li Lin; Sheng-Yang Lee; Long-Yi Lee; Wen-Ta Chiu; Che-Tong Lin; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2006)